Effectiveness of joyful game-based blended learning method in learning chemistry during COVID-19 - Sripriya Sundaram; Rajendran Ramesh (International Journal of Evaluation and Research in Education (IJERE), 2022)
The recent introduction of joyful learning in National Education Policy (NEP) 2020 created great interest among students and is predicted to be the most suitable learning method for 21st-century learners. Game-based learning enhances education making all educational games increasingly popular. Learning efficiency can be enhanced through educational games. This article purposes to examine the efficiency of the game-based joyful blended learning method in learning chemistry, periodic table elements (1 to 30) among tenth standard students. The main purpose of the current study was to assist secondary school students to learn science-related ideas via participating in educational card games and using digital media for learning concepts. The educational advantages of the game in terms of learning performance, as well as students’ views of its integration into scientific learning, were studied. A quasi-experimental technique was used to obtain the study’s goal. The sample comprises 240 students studying the tenth standard in 4 different private CBSE schools in Palakkad district, Kerala, India. The pretest, posttest, gain scores, and retention scores were compared. The study's results indicated that there is a substantial mean score variation in learning chemistry (elements) between pretest, posttest, and retention tests of students in the experimental and control group. The students developed positive attitudes towards the usage of educational cards in learning Chemistry. The developed game-based joyful blended learning method develops reflective thinking and self-regulated learning among students.